The Archaeology of Population Dynamics - Barrett, John C. (Current Swedish Archaeology, 2019)
A critical evaluation of the recent interpretation of aDNA data that link the adoption of domesticated plants and animals across Europe with a migration of human populations from southwest Asia and the Aegean. These data have been used to question previous models that argued for the uptake of farming by indigenous hunter-gatherer populations.